Mediating Effect of Social Media in The Relationship between Brand Deformity and Brand Loyalty - Deivayanai, S; Chandran , M. (International Journal of Accounting and Economics Studies, 2025)
The phenomenon of social media marketing, with the help of smartphones available to each consumer in the world, can be easily communicated by marketers, manufacturers, and dealers to introduce their products with the reputation of brands and offer their marketing techniques. The mediating effect of derived from a social media factor in finding the relationship between entities. The convenience sampling and snowball sampling methods were applied to collect 450 responses from social media users in Chennai city. It is concluded that the social media marketing factors are a mixture of five important predominant namely receiving, reviewing, relating, sharing, and interacting. The social media users of consumers arbitrarily and capriciously received the messages through social media platforms, and technical knowledge motivates them to review continuously and relate their perception with the present product for brand deformity and brand loyalty.